Age and temperature effects on accumulation of carotenoids in ladybirds. - Nedvěd, Oldřich; Aslam, Muhammad; Abdolahi, R.; Sakaki, S.; Soares, A.O. (IOBC, 2019)
Carotenoids are important pigments of ladybirds providing bright red colouration. We measured the rate of deposition of carotenoids with age in elytra of two ladybird species in ethanol extracts, as well effects of sex and temperature. In Coccinella undecimpunctata, content of carotenoids continued to increase after 60 days of adult age at both 20 and 25 °C. Males had slightly higher pigment concentration than females. Carotenoid content in adult Harmonia axyridis (forma succinea) increased up to four months of the adult stage. No difference was found between individuals with contrasting extent of melanic pattern or between sexes. The trend of increase was between Holling functional types 1, 2, and 3. In a later experiment, the carotenoid content increased up to three months of the adult stage similarly for three levels of melanisation. There was no decrease of carotenoids in individuals with large melanic patterns. This means that carotenoids are not deposited under black spots. After four months, there was little decrease in carotenoid content. Thus, the trend was between functional types 2, 3, and 4. Slower rate of carotenoid deposition during adult stage after 1 week and 1 month was observed at higher temperatures (25, 30 °C) than at lower ones (15, 20 °C).
Keywords: colouration; ladybirds; pattern; pigment; time